Pengujian Empiris Pengungkapan CSR Terhadap Firm Size - Malik, Abdul (Graha Akuntansi, 2022)
The aim of this research is to know: (1) The influence of Corporate Social Responsibility to firm value (2) The influence of Percentage of management ownership as the moderating variable in relations between Corporate Social Responsibility and firm value. The research sample is non-financial sector in 2005 by using method of purposive sampling. There are 41 company fulfilling criterion as this research sample. The methode analysis of this research used multiple regression analysis. The result of study show that (1) Simultaneously the effect of Corporates Social Responsibility, percentage of management ownership and interaction between Corporate Social Responsibility and Percentage of management ownership on firm value was significant and. (2) Partially, only percentage of management ownership have an effect on significant to firm value, while other variables in this research have not an effect on significant to fim value.